EXPERIENCED ENGLISH TEACHERS’ PERSPECTIVES ON THE FULFILLMENT OF ONE-PAGE LESSON PLAN PRINCIPLES AT SMAN 1 SINGARAJA - Januarta, Putu Agus; Utami, Lokita Purnamika; Utami, Ida Ayu Made Istri (Universitas Nahdatul Ulama Surabaya, 2021)
Abstract: This research aims at analyzing the experienced English teachers’ perspectives on the fulfillment of one-page lesson plan principles at SMAN 1 Singaraja. The research design used a case study qualitative approach. The research subjects were 2 experienced English teachers. The data collection procedure used in this study was an in-depth interview. The instruments of data collection procedure used was interview guides. The results revealed that the experienced English teachers’ perspectives were positive as the teachers believed that the one-page lesson plan was more efficient, effective, and more student-oriented so that the teachers could make simple lesson plan easily. These results showed that the principles of developing the one-page lesson plan have been implemented well based on the Circular Letter Number 14 of 2019 concerning Simplification of the Lesson Plan. Besides, the policy on the simplification of lesson plan needs to be maintained as it gains positive responses from the experienced English teachers. Keywords: perspectives, one-page lesson plan princples, experienced teachers Abstrak: Penelitian ini bertujuan untuk menganalisis perspektif guru bahasa Inggris berpengalaman tentang pemenuhan prinsip RPP satu halaman di SMAN 1 Singaraja. Desain penelitian menggunakan pendekatan kualitatif studi kasus. Subjek penelitian adalah 2 orang guru bahasa Inggris yang berpengalaman. Prosedur pengumpulan data yang digunakan adalah wawancara mendalam. Instrumen prosedur pengumpulan data yang digunakan adalah pedoman wawancara. Hasil penelitian mengungkapkan bahwa perspektif guru bahasa Inggris yang berpengalaman adalah positif karena guru tersebut meyakini bahwa RPP satu halaman lebih efisien, efektif, dan lebih berorientasi pada siswa sehingga guru tersebut dapat membuat RPP yang sederhana dengan mudah. Hasil ini menunjukkan bahwa prinsip-prinsip penyusunan RPP satu halaman telah dilaksanakan dengan baik sesuai dengan Surat Edaran Nomor 14 Tahun 2019 tentang Penyederhanaan Rencana Pelaksanaan Pembelajaran (RPP). Selain itu, kebijakan penyederhanaan RPP ini perlu dipertahankan karena mendapat respon positif dari para guru bahasa Inggris yang berpengalaman. Kata Kunci: perspektif, prinsip RPP satu halaman, guru berpengalaman